NA IGREJA, NO SINDICATO, NA UNIVERSIDADE, NA RUA: os movimentos feministas no “Portal da Amazônia” - VIANA, Maria dos Remédios Brito (2022)
Imperatriz stands out as a medium-sized city, a regional economic hub, located in the southwest region of Maranhão State on the border of the North and Northeast regions of Brazil, marked by agrarian conflicts, disputes for land, urban violence, high contract killing rates in its recent past (TEIXEIRA, 2016), massive presence of women as household heads and the remarkable conservative role of Christian religions. Unveiling how women from this place organize their agendas, discussions, gathering places, meeting and protest spaces marked by female presence is essential. Therefore, we aim to understand the sociability networks composed by women from Imperatriz linked to groups which call themselves feminists or, that do not recognize themselves as feminists however, their agendas contemplate the struggle for gender equality. We are also interested in knowing the discussions that such groups raise, their claims, articulations, participation in the sociopolitical context, their conflicts and relationship with Imperatriz society as well as the effects and resonances of these mobilizations in the public policies network in the municipality. Using the Oral History method (ALBERTI, 2005) crossed by Intersectionality (HILL COLLINS; BILGE, 2020), we prioritized interviews wAith protagonists linked to women's groups that emerged within the Catholic Church; women from the political context, from social movements, from union militancy and from the academy. The theoretical reflections around feminism that were focused in this paper come from authors such as Simone de Beauvoir, Heleieth Saffioti, Gloria Anzaldúa, Kimberlé Crenshaw, Nancy Fraser, María Lugones, Ângela Davis, Mary Ferreira, Carla Akotirene, Heloísa Buarque de Hollanda, Audre Lorde, Patricia Hill Collins, Lélia González and Bell Hooks. We conclude that there are several feminist movements in the “Portal da Amazônia”, and historically they occupy spaces such as the Church, unions, universities and the streets, with agendas demarcated by struggles in favor of women protagonism, job and income generation, anti-capitalist feminism constructed from the class struggle and in the midst of social movements and in topics related to sexual and identity freedom, explored and developed in the social and virtual environment (through social networks such as Facebook, Instagram).